Employee Engagement And Interpersonal Communication Training To Improve Consumer Service For Baristas Composure In Medan City - Asra Maulana; Fajar Ahmad Lazuardy; Putri Balqis; Theresia Ribka Purba (Yayasan Rahmat Islamiyah, 2026)
This activity aims to improve competitiveness and service quality through employee engagement and interpersonal communication training for Composure baristas in Medan City. The study employs a qualitative research method with an observational approach conducted over six weeks, comprising two weeks of pre-training observation, four weeks of training implementation (five structured sessions), and two weeks of post-training observation, involving ten barista informants. The training program included three main strategies: presentations on the importance of employee engagement and interpersonal communication, service role-plays and simulations, and evaluation of simulation results. The activity results reveal four main themes. First, the initial level of barista employee engagement and interpersonal communication fell into the low to moderate category before the training. Second, the training program successfully increased barista awareness and motivation regarding the importance of emotional involvement at work. Third, barista interpersonal communication skills showed significant development after the training, especially in empathy and active listening. Fourth, customer service quality improved as reflected by changes in barista behavior when interacting with customers. This study concludes that integrated training focusing on engagement and communication is a relevant and effective intervention to improve service quality in the coffee shop industry.